Is scanning for vasa previa important for singleton pregnancies that started as multiple conceptions?. (July 2019) - Melcer, Yaakov; Pekar-Zlotin, Marina; Wolf, Brian; Betser, Moshe; Dvash, Shira; Zilberman Sharon, Nataly; Maymon, Ron
Abstract: Objectives: Vasa previa (VP) is a congenital placentation disorder in which fetal vessels run across the internal os of the cervix under the fetal presentation. This rare condition is associated with a high rate of perinatal morbidity and mortality when undetected before delivery. Roughly 85% of all cases of VP can be associated with one or more identifiable risk factors including in-vitro fertilization (IVF), multiple gestations, bilobed, succenturiate or low-lying placentas, and velamentous cord insertion (VCI). Recent evidence indicates the need for standardized prenatal targeted scanning protocols of pregnancies at risk of VP. The present study reports on pregnancies that began with multiple gestations but ended with a single fetus diagnosed with VP. Study design: We retrospectively collected and reviewed medical records from 2006 to 2018 of early multiple pregnancies that ended with a single fetus diagnosed with VP in our medical center, including three cases of twin gestation complicated by a vanishing twin and a case of multifetal reduction in triplet pregnancy. This retrospective cohort study was approved by our Institutional Clinical Research Committee. Results: The database search identified 50 pregnancies that started as multiple gestations but continued as singletons. Of these, 4 pregnancies were diagnosed with VP, for a prevalence of 8.0%. For two of the four cases, the diagnosis was made during delivery as expressed by a low Apgar score at 1 and 5 min, a low cord blood pH value, newborn resuscitation, blood product transfusion, and NICU supervision. There was a statistically signiﬁcant difference in the prevalence of VP in pregnancies that started as multiple gestations but continued later as singletons compared to multiple pregnancies (8.0% vs. 0.2% respectively, p < 0.0001). The OR for VP in pregnancies that started as multiple gestations but continued as singletons was 41.1 (95% CI, 12.77–131.94). Conclusions: Our findings suggest there is an increased risk of VP in conceptions that started as viable multiple gestations but continued later as singletons. If our findings supported by others, it may be prudent to consider all twins at the beginning of pregnancy to be at risk for VP, irrespective of the actual number of life fetuses at later stages of gestation.